The market potential and financial feasibility of cable car tourist attraction development in Pelaga, Bali, Indonesia - I Gusti Bagus Rai Utama; Putu Chris Susanto; Christimulia Purnama Trimurti; Ni Putu Dyah Krismawintari (Institute of Advanced Engineering and Science, 2022)
The purpose of this work is to carry out consumer and investor behavior through a feasibility study of cable car tourist attractions in agritourism in Pelaga Village, Petang district, which focuses on studying marketing and financial perspective. This research uses observation and feasible study methods based on marketing theory, and investment financial management theory. It is highly likely by potential tourists as an attraction that can openly present natural beauty, as an environmentally friendly tourist attraction, a unique tourist attraction in Bali, will provide public facilities, telecommunications, restaurants, and agro product market centers, proximity to the city center, availability of transportation to the location, easy access to locations, and community friendliness towards tourist arrivals. The economic aspect where analysis of market opportunities is based on estimated sales data for four types of services: cable cars, restaurants, UFO glass platform attraction, and under the park and agritourist. The findings of this study reinforce the method and theory that business-oriented development planning must go through a feasible study of at least two important aspects, namely aspects of market potential, and aspects of investment management which are expected to be profitable for investors.